Essential amino acid analysis of selected Philippine vegetables and fruits - Sutaria, Piloo B.; San Diego, Ma. Lourdes (1982)
Thirty-nine varieties of vegetable and twenty-one varieties of fruits were investigated as to their amino acids contents. All the amino acids with the exception of cysteine,cystine, hydroxyproline and tryptophan were determined in Durrum 400 D Amino Acid Analyzer. These four amino acids were somehow destroyed during acid hydrolysis.Also, all the varieties of vegetables and fruits were chemically investigated as to the moisture, total nitrogen, crude and protein and allpha-amino nitrogen contents.